Highly confined in-plane propagating exciton-polaritons on monolayer semiconductors. (29th June 2020) - Epstein, Itai; Chaves, André J; Rhodes, Daniel A; Frank, Bettina; Watanabe, Kenji; Taniguchi, Takashi; Giessen, Harald; Hone, James C; Peres, Nuno M R; Koppens, Frank H L
Abstract: 2D materials support unique excitations of quasi-particles that consist of a material excitation and photons called polaritons. Especially interesting are in-plane propagating polaritons, which can be confined to a single monolayer and carry large momentum. In this work, we theoretically predict the existence of a new type of in-plane propagating polariton, supported on monolayer transition-metal-dicalcogonides (TMDs) in the visible spectrum. This 2D in-plane exciton-polariton (2DEP) is described by the coupling of an electromagnetic light field with the collective oscillations of the excitons supported by monolayer TMDs. We experimentally demonstrate the specific conditions required for the excitation of the 2DEP and show that these can be achieved if the TMD is encapsulated with hexagonal-boron-nitride (hBN) and cooled to cryogenic temperatures. In addition, we compare the properties of the 2DEP with those of the surface-plasmon-polariton at the same spectral range, and find that the 2DEP exhibit over two orders-of-magnitude larger wavelength confinement. Finally, we propose and numerically demonstrate two configurations for the possible experimental observation of 2DEPs.